2004
DOI: 10.2320/matertrans.45.2665
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution in Friction Stir Welded 1050 Aluminum and 6061 Aluminum Alloy

Abstract: The microstructure of friction stir welded 1050 aluminum and 6061 aluminum alloy was observed by a metallographic technique, transmission electron microscopy, electron backscatter diffraction pattern and optical microscopy. In the stir weld zone, the microstructure of welded 1050 aluminum was significantly different from that of the welded 6061 aluminum alloy. In the case of welding 1050 aluminum, there was a comparatively uniform microstructure in the stir weld zone, not a wedge-shaped microstructure formed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Grain boundary characteristics have significant meaning for investigating the recrystallization and superplasticity mechanisms. [18][19][20][21][22] It was reported that the percentage of the HAGBs in the SZ of FSW aluminum alloys was higher than in that processed by conventional thermal working techniques. [18] Liu et al [19] indicated that for FSW cold-rolled 1050 aluminum alloy, the percentages of the HAGBs of the PM and the SZ were 32 and 70 pct, respectively.…”
Section: A Microstructural Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grain boundary characteristics have significant meaning for investigating the recrystallization and superplasticity mechanisms. [18][19][20][21][22] It was reported that the percentage of the HAGBs in the SZ of FSW aluminum alloys was higher than in that processed by conventional thermal working techniques. [18] Liu et al [19] indicated that for FSW cold-rolled 1050 aluminum alloy, the percentages of the HAGBs of the PM and the SZ were 32 and 70 pct, respectively.…”
Section: A Microstructural Evolutionmentioning
confidence: 99%
“…[18][19][20][21][22] It was reported that the percentage of the HAGBs in the SZ of FSW aluminum alloys was higher than in that processed by conventional thermal working techniques. [18] Liu et al [19] indicated that for FSW cold-rolled 1050 aluminum alloy, the percentages of the HAGBs of the PM and the SZ were 32 and 70 pct, respectively. Mishra and Mahoney, [20] Norman et al, [21] and Liu et al [22] reported that in the SZ of FSW aluminum alloys, the percentage of the HAGBs is 85 to 97 pct.…”
Section: A Microstructural Evolutionmentioning
confidence: 99%
“…[8] The tool penetration process and the factors determining weld mechanical properties have been investigated during spot welding of Al-alloy and Mgalloy sheet materials. [9][10][11][12] Although the microstructural features and mechanical properties of Al 5754 and Al 6061 friction stir seam welds have been studied extensively, [13][14][15][16][17][18][19][20][21] this is not the case in Al 5754 and Al 6061 friction stir spots welds made using a range of tool rotational speed settings.…”
Section: Introductionmentioning
confidence: 99%